Teachers’ perspectives on the challenges of implementing inclusive education in Tanzanian rural schools - Kanyopa, Theresia Joakim; Mokhele-Makgalwa, Matseliso (Edelweiss Applied Science and Technology, 2025)
This paper explores teachers’ perspectives on the challenges of implementing inclusive education in Tanzanian rural schools. The study was prompted by findings from previous research studies on inclusive education in Tanzania, which revealed that teachers in rural schools face challenges in implementing inclusive education. The study is underpinned by the Learner Integration Wheel (LIW) theory of practice, which advocates the implementation of inclusive education through regular learner integration in schools. Collaboratively, the LIW theory of practice brings together the school, curriculum developers, and the school community as the key players towards the implementation of inclusive education. An interpretive paradigm under a qualitative approach, and a multiple case study research design, were adopted to explore teachers’ perspectives on the researched issue. Qualitative methods, including interviews and reflective essay writing, were used to generate data from eight participants (8 teachers), four from primary schools, and four from secondary schools. The study found that teachers in Tanzanian rural contexts are not well prepared to implement inclusive education in schools. Considering the findings, this study reports that there is a need for proper training to equip teachers with skills and the ability to support learners, specifically those with learning barriers.